2018
DOI: 10.1080/17461391.2018.1534990
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different dosages of caffeine administration on wrestling performance during a simulated tournament

Abstract: The aim of the present study was to investigate the effects of different forms of caffeine administration on physical performance during a simulated wrestling tournament. In a double-blind and randomized experiment, twelve male freestyle wrestlers competed in a simulated wrestling tournament (5 wrestling matches consisting of 2 × 3-min wrestling rounds) following the ingestion of: a placebo, a high-dose of caffeine (10 mg/kg), a moderate-dose caffeine (4 mg/kg), a repeated-dose caffeine (2 mg/kg before each ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 40 publications
0
42
0
1
Order By: Relevance
“…Souissi et al [52], however, noted that CAF ingestion improves peak and mean power after morning compared to afternoon supplementation. CAF effectiveness was also investigated in wrestling [53, 54], taekwondo [55, 56], Brazilian jiu-jitsu (BJJ) [49, 57] and boxing [58]. Four [54] and 5 mg/kg [53] doses were ineffective; only 10 mg/kg CAF [54] improves performance in wrestlers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Souissi et al [52], however, noted that CAF ingestion improves peak and mean power after morning compared to afternoon supplementation. CAF effectiveness was also investigated in wrestling [53, 54], taekwondo [55, 56], Brazilian jiu-jitsu (BJJ) [49, 57] and boxing [58]. Four [54] and 5 mg/kg [53] doses were ineffective; only 10 mg/kg CAF [54] improves performance in wrestlers.…”
Section: Discussionmentioning
confidence: 99%
“…CAF effectiveness was also investigated in wrestling [53, 54], taekwondo [55, 56], Brazilian jiu-jitsu (BJJ) [49, 57] and boxing [58]. Four [54] and 5 mg/kg [53] doses were ineffective; only 10 mg/kg CAF [54] improves performance in wrestlers. Further, supplementation with 5 mg/kg CAF produced mixed results in taekwondo athletes [55, 56]; 3 mg/kg enhances combat intensity and muscular performance in BJJ [49, 57] and 6 mg/kg induces greater duration of high-intensity actions in boxing [58].…”
Section: Discussionmentioning
confidence: 99%
“…In future studies it should be recommended to determine the ergogenic effects of caffeine on both upper and lower limbs, by subjecting the boxers to several bouts of a specific test that includes the four extremities. In this sense, Negaresh et al [68], observed during a simulated wrestling tournament that an individualized caffeine supplementation protocol should be implemented when physical performance is expected to be reduced (i.e., usually during the latter combat rounds).…”
Section: Discussionmentioning
confidence: 99%
“…Kafeinin anaerobik performansa pozitif etkilerinin olduğunu gösteren bu sonuçların aksine voleybol ve futbolcularda anaerobik performansa etkisi olma-dığını belirten araştırma sonuçları da bulunmaktadır. 6,21,[52][53][54][55][56] Kafein tüketiminin erişkin erkeklerde anaerobik performansa etkisinin olmadığını, hatta maksimum güç çıktısında düşüşe neden olduğunu, izokinetik kuvvete etkisi olmadığını gösteren çalışmalar literatürde bulunmaktadır. 2,29,30,46,57,58 Kafeinin anaerobik performansa etkileri ile ilgili çalışmaların büyük çoğunluğu, aktif erişkin erkek bireyler üzerinde yapılmış araştırmalardır.…”
Section: Discussionunclassified